ACE2‐EPC‐EXs protect ageing ECs against hypoxia/reoxygenation‐induced injury through the miR‐18a/Nox2/ROS pathway. Issue 3 (24th January 2018) - Zhang, Cheng; Wang, Jinju; Ma, Xiaotang; Wang, Wenjun; Zhao, Bin; Chen, Yanfang; Chen, Can; Bihl, Ji C.
Abstract: Oxidative stress is one of the mechanisms of ageing‐associated vascular dysfunction. Angiotensin‐converting enzyme 2 (ACE2) and microRNA (miR)‐18a have shown to be down‐regulated in ageing cells. Our previous study has shown that ACE2‐primed endothelial progenitor cells (ACE2‐EPCs) have protective effects on endothelial cells (ECs), which might be due to their released exosomes (EXs). Here, we aimed to investigate whether ACE2‐EPC‐EXs could attenuate hypoxia/reoxygenation (H/R)‐induced injury in ageing ECs through their carried miR‐18a. Young and angiotensin II‐induced ageing ECs were subjected to H/R and co‐cultured with vehicle (medium), EPC‐EXs, ACE2‐EPCs‐EXs, ACE2‐EPCs‐EXs + DX600 or ACE2‐EPCs‐EXs with miR‐18a deficiency (ACE2‐EPCs‐EXs anti‐miR‐18a ). Results showed (1) ageing ECs displayed increased senescence, apoptosis and ROS production, but decreased ACE2 and miR‐18a expressions and tube formation ability; (2) under H/R condition, ageing ECs showed higher rate of apoptosis, ROS overproduction and nitric oxide reduction, up‐regulation of Nox2, down‐regulation of ACE2, miR‐18a and eNOS, and compromised tube formation ability; (3) compared with EPC‐EXs, ACE2‐EPC‐EXs had better efficiencies on protecting ECs from H/R‐induced changes; (4) The protective effects were less seen in ACE2‐EPCs‐EXs + DX600 and ACE2‐EPCs‐EXs anti‐miR‐18a groups. These data suggest that ACE‐EPCs‐EXs have better protective effects on H/R injury in ageing ECs which could be through their carried miR‐18a and subsequently down‐regulating the Nox2/ROS pathway.